SURVEY OF THE PHYSICAL FITNESS OF MENTALLY RETARDED CHILDREN - Septaliza Dewi (Program Pascasarjana Universitas Negeri Jakarta, 2021)
This study aims to determine the level of physical fitness of mild type mentally retarded children at SLB Karya Ibu Palembang. The research technique used is descriptive research using survey methods with data collection techniques using tests and measurements with TKJI. The population in this study were 18 students with mild mental retardation in 2019/2020 at SLB Karya Ibu Palembang. The data analysis technique uses descriptive percentages. The results of this study are: Based on the results of the description, data analysis and discussion, it can be concluded that the physical fitness level of the students of SLB Karya Ibu Palembang in the 2019/2020 school year is in the very low category, this is evidenced by the percentage level results. Physical fitness of the students of SLB Karya Ibu Palembang for the 2019/2020 school year, where there are 15 boys with mild mental retardation age 10-12 years. In accordance with the table of physical fitness norms for mild mentally retarded children 10-12 years old in SLB Karya Ibu, which is included in the Very Good (VG) category as many as 0. children (0%),good (G) as many as 2 children (13.33%), medium (M) as many as 4 children (26.67%), low (L) as many as 6 children (40%), and very low (VL) as many as 3 children (20%). Based on the number of children with mild mental retardation, girls aged 10-12 years, as many as 3 girls. In accordance with the table of physical fitness norms for mild mentally retarded children 10-12 years, in Karya Ibu SLB which is included in the very good category (VG) as many as 0 children (0%), good (G) as many as 0 children (0%), medium (M ) as many as 0 children (0%), low (L) as many as 2 children (66.67%), and very low (VL) as many as 1 child (33.33%).Based on the results of the description, data analysis and discussion, it can be concluded that the physical fitness level of the SLB Karya Ibu students for the 2019/2020 school year is included in the low category, this is evidenced by the results of the percentage of physical fitness levels of SLB Karya Ibu students for the 2019/2020 school year, where students boys and girls in the low category.